ADA Deficiency: Evaluation of the Clinical and Laboratory Features and the Outcome - BARIŞ, SAFA (SPRINGER/PLENUM PUBLISHERS, 2018)
Adenosine deaminase (ADA) deficiency is an autosomal recessive primary immunodeficiency. It results in the intracellular accumulation of toxic metabolites which have effects particularly on lymphocytes and the brain. The aim of this study was to evaluate the outcome of 13 ADA-deficient patients. We planned to evaluate their clinical and laboratory findings before and after enzyme replacement therapy (ERT), allogeneic hematopoietic stem cell transplantation (aHSCT), and hematopoietic stem cell gene therapy (HSCGT). Measurement of ADA enzyme activity and metabolites and sequencing of the ADA gene were performed in most of the patients with ADA deficiency. One of the patients with late-onset ADA deficiency was diagnosed by the help of primary immunodeficiency panel screening. Ten out of 13 patients were diagnosed as SCID, while 3 out of 13 were diagnosed as delayed-/late-onset ADA deficiency. Late-onset ADA deficiency patients had clinical and laboratory findings of combined immunodeficiency (CID). Eight patients with ADA-SCID were found to have higher levels of ADA metabolite (dAXP%) (62.1% (34.6-71.9)) than 3 patients with delayed-/late-onset ADA deficiency (6.9% (2.1-8.9). All but one patient with SCID had T-B-NK- phenotype, one had T-B-NK+ phenotype. Genetic defect was documented in 11 patients. Four out of 11 patients had compound heterozygous defects. Three out of 4 patients with compound heterozygous defects had delayed-onset/late-onset ADA deficiency. Seven out of 11 patients with SCID had homozygous defects. Five out of 7 had the same homozygous indel frameshift mutation (c.955-959delGAAGA) showing a founder effect. There were two novel splice site defects: one (IVS10+2T > C) was heterozygous in a patient with late-onset ADA deficiency, and the other was homozygous (IVS2delT+2) in a SCID patient. Other defects were missense defects. Nine out of 13 patients were put on pegylated ADA ERT. Four out of six patients were transplanted without using a conditioning regimen. HSCGT was performed to one of the patients. The genetic diagnosis of SCID is utmost important. There is a chance to give ERT before the definitive therapy if the patient with SCID/CID has ADA deficiency. Although ERT was insufficient to restore a normal immune function in ADA-SCID patients, it was useful to improve and stabilize the clinical status before curative therapy (aHSCT/HSCGT). Enzyme replacement therapy was successful in patients with late-/delayed-onset ADA deficiency who presented with the features of combined immunodeficiency. Gastrointestinal polyposis in a patient with late-onset ADA deficiency may be an association or a coincidental finding. Intermittent neurodevelopmental evaluation especially for hearing impairment should be performed in most of the ADA-deficient patients. This may alleviate the speech delay and cognitive abnormalities which may be observed in the follow-up.
Keywords: Late-onset adenosine deaminase deficiency; SCID; ADA enzyme replacement therapy; SEVERE COMBINED IMMUNODEFICIENCY; ADENOSINE-DEAMINASE DEFICIENCY; SINGLE-CENTER EXPERIENCE; GENE-THERAPY; PHENOTYPE; GENOTYPE; MUTATION; IMMUNITY; DISEASE; ONSET